The Effect of Adding Cricket Flour (Gryllus bimaculatus) as a Substitute for Soybean Meal in Finisher Feed on Broiler Chicken Welfare - Lazuardi, Pahlawan Bintang; Ni'am, Muhammad Nidhomun; Widiastuti, Sri (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
The issue of limited soybean meal availability and dependence on imports in Indonesia necessitates the search for alternative protein sources for animal feed. This study aimed to evaluate the impact of partially replacing soybean meal with cricket flour in the finisher feed of broiler chickens on breast dirtiness, footpad dermatitis (FPD), and hock burn. A total of 100 male Indian River broiler chickens were raised for 5 weeks in a closed-house system, divided into two treatment groups with 5 replications, each consisting of 10 chickens. The birds were housed in pens measuring 1.5 m x 0.75 m. The feeding treatments began during the finisher phase (age 21–35 days), with P0 containing 28.5% soybean meal and P1 containing 18.5% soybean meal + 10% cricket flour. Data on breast dirtiness, FPD, hock burn, and behavior were collected from days 33 to 35 and subsequently scored. The data were analyzed statistically using the Mann-Whitney test with the aid of the Statistical Package for Social Science (SPSS). The results showed that substituting 10% of soybean meal with cricket flour significantly reduced footpad dermatitis (P=0.02), while no significant differences were found in hock burn and breast dirtiness (P>0.05). Based on the findings of this study, it can be inferred that partially substituting soybean meal with cricket meal has the potential as an alternative protein source without causing welfare issues in broiler chickens.